McPhee's Children [float] - Cal Poly San Luis Obispo Audio-Visual Department::::::::: (1965)
Paper mache puppets were made of Julian Mcphee's 'children' (actually, the students of Cal Poly, represented as Sr, Jr, Soph, and Frosh) and brought through the Homecoming Parade on a float.